Moribane forest reserve in Mozambique : land use and its impacts on biodiversity and livelihoods - Dukpa, Rebecca (2018)
Most of the people in Mozambique depend their daily livelihoods on small-scale agriculture, where also forests are converted into croplands. However, conversion of forest to croplands is the largest cause of land-use change emissions globally. This study was conducted in three phases. Firstly, existing research articles were studied from Mozambique. Secondly, 51 socio-economic interviews were conducted among the rural communities in Moribane. Thirdly, the area and land use were studied by conducting field walks along the newly built and paved N260, Chimoio-Mossurize road. This study aimed to determine how the land is used and what are the main crops cultivated in small-scale agriculture in Moribane. Additionally, this study aimed to show the impacts the road has caused, the positive and negative impacts on local communities and on the natural environment. The research showed connections between agricultural activities, land use changes and their socio-ecological impacts. The most important crops cultivated in the area were maize, banana and sesame. The local people found the effects of new road to be mostly positive and providing benefits for their daily lives, however based on the results, negative impacts were also present, such as erosion, increased traffic and accidents. Small-scale agriculture is under increasing global pressure, while at the same time poorer households depend greatly on small-scale farming and are among the most vulnerable people when facing environmental degradation.